Effects of Phosphatidylinositol 4,5-Bisphosphate and Phosphatidylinositol 4-Phosphate on a Na(+)-Gated Nonselective Cation Channel - Zhainazarov, Aslbek B. (J Neurosci, 1999)
Olfactory receptor neurons in the lobster express a nonselective cation channel that is activated by intracellular Na(+) and carries a substantial part of the depolarizing receptor current. Here, we show that phosphatidylinositol 4,5-bisphosphate [PI(4,5)P(2)] and phosphatidylinositol 4-phosphate [PI(4)P] applied to the intracellular face of cell-free patches activate the channel in the absence of Na(+)and that antibodies against the respective phospholipids irreversibly inhibit the evoked activity. Further, we show that applying PI(4,5)P(2) or PI(4)P in the presence of Na(+) decreases the concentration of Na(+) required to activate the channel from an EC(50) of 74 to 22 mm for PI(4,5)P(2) and to 29 mm for PI(4)P, respectively. Na(+)-gated channel activity was irreversibly inhibited by monoclonal antibodies against PI(4,5)P(2) and PI(4)P in patches never exposed to exogenous phosphatidylinositols, suggesting that endogenous inositol phospholipids are required for the activation of the channel by intracellular Na(+). Our findings suggest that PI(4,5)P(2) and/or PI(4)P may serve as intracellular signaling molecules in these primary sensory neurons and provide a general mechanism to explain how the sensitivity of Na(+)-gated channels to Na(+) could be much greater in intact cells than in excised membrane patches.